2022
DOI: 10.2147/ccid.s377029
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Teledermatology During the COVID-19 Pandemic: A Narrative Review

Abstract: Teledermatology represented one of the most important and useful tools during the COVID-19 pandemic era. Indeed, due to the severe restriction, and to reduce the spread of the infection, different measures were applied among different countries and hospitals to ensure a continuity of care for patients. In this scenario, teledermatology played a central role, especially in the management of patients suffering from chronic inflammatory skin diseases. The aim of this narrative review is to describe the role of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 119 publications
0
8
1
Order By: Relevance
“…A survey-based study including 246 psoriatic patients in stable clinical remission undergoing biologic treatment showed that 118 patients (48%) preferred telemedicine over a face-to-face visit, saving time and reducing the risk of contracting COVID-19 infection. 4 Although online consultation is a good alternative and a useful weapon for the chronic management of psoriatic patients, 5 few patients in our survey increased their use of online consultation because of little knowledge about online consultation. Doctors could introduce online consultation to patients to help address this problem.…”
Section: Discussionmentioning
confidence: 91%
“…A survey-based study including 246 psoriatic patients in stable clinical remission undergoing biologic treatment showed that 118 patients (48%) preferred telemedicine over a face-to-face visit, saving time and reducing the risk of contracting COVID-19 infection. 4 Although online consultation is a good alternative and a useful weapon for the chronic management of psoriatic patients, 5 few patients in our survey increased their use of online consultation because of little knowledge about online consultation. Doctors could introduce online consultation to patients to help address this problem.…”
Section: Discussionmentioning
confidence: 91%
“…[79][80][81] Fortunately, their safety was confirmed even during COVID-19 pandemic 82 which led to the adoption of several measures in order to contain the spreading of the infection allowing the continuity of biologic treatment, opening new era also after COVD-19 pandemic period. 25,83,84 However, the introduction of COVID-19 vaccination newly raised doubt on their efficacy and safety among psoriasis patients receiving biologics. Indeed, the immunologic reaction and immune system dysregulation caused by vaccination may lead to epidermal changes and onset or worsening of certain cutaneous diseases such as psoriasis 85 Moreover, the induction of neutralizing antibodies and T-cell responses by vaccines can lead to increased IFNγ and TNFα production.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 22 Access to health care facilities was also limited to severe cases, leading to a complete revolution of the daily dermatological practice. 17 , 23 On the other hand, the need for dermatologists increased during the pandemic for several reasons such as the frequent association of SARS-CoV-2 infection with skin disorders such as erythematous rash, the increased use of protective devices and hand sanitizers worsening pre-existing skin conditions and increasing dermatitis, dermatological consultations on interactions of immunomodulating therapies for chronic inflammatory diseases. 24 Similarly, the use of dermatology was also required during the COVID-19 vaccination campaign, due to the cutaneous reactions following COVID-19 vaccination.…”
Section: Teledermatology and Covid-19: Before And Aftermentioning
confidence: 99%